Ashore and Afloat : the British Navy and the Halifax Naval Yard Before 1820. - Gwyn, Julian (University of Ottawa Press, 2004)
Ashore and Afloat tells the early history of the Halifax Naval Yard. From the building of the yard and its expansion, to the people involved in the enterprise, to the nuts and bolts of buying the masts and paying the bills, Julian Gwyn's history of the Halifax Naval Yard leaves no stone unturned. Dozens of illustrations and copious appendices, including a biographical directory, accompany this compelling history.